Subband adaptive chip equalization for interference suppression in DS-UWB - Ng, Yin Hoe; Mohamad, Hafizal; Chuah, Teong Chee (IEICE-INST ELECTRONICS INFORMATION COMMUNICATIONS ENG, 2007)
We propose a subband adaptive chip equalizing (SACE) receiver for high-speed direct-sequence ultra-wideband (DS-UWB) communications to efficiently suppress intersymbol interference (ISI) and multiple-access interference (MAI) in short-range indoor networks. The SACE receiver exploits the pre-whitening effect of the filter banks to reduce the eigenvalue spread of the input signal covariance matrix. Numerical results show that the proposed receiver significantly outperforms the fullband adaptive chip equalizing ( FACE) receiver while maintaining a lower complexity.